Characterization of nano-sized CdS-Ag2S core-shell nanoparticles using XPS technique - Hota, G.; Idage, Susheela B.; Khilar, Kartic C. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2007)
This paper reports the use of X-ray photoelectron spectroscopy (XPS) method for the characterization of surface composition of core and shell nanoparticles. The core and shell nanoparticles were synthesized using sodium bis(2-ethylhexyl) sulfosuccinate (AOT)/n-heptane/water microemulsion technique. The post-core and partial microemulsion methods have shown promise for core and shell formation and enhanced stability and sphericity of the semiconductor nanoparticles. In addition to above technique, the core-shell nanoparticles have also been characterized using SEM-elemental detection X-ray analysis (EDAX) and results are discussed. The XPS studies of US, Ag2S, and CdS-Ag2S nanoparticles prepared by post-core/partial microemulsion methods were carried out and results are compared with physical mixing of US and Ag2S nanoparticles. The Ag/Cd atomic ratio is found to be 5 and 10 as determined by XPS methods for nanoparticles prepared by using post-core and partial microemulsion methods, respectively. These results show the formation of core and shell nanoparticles. (c) 2006 Elsevier B.V. All rights reserved.